Wonderful things : a history of Egyptology ; 1: From antiquity to 1881 - Thompson, Jason (The American University in Cairo Press, 2015)
The discovery of ancient Egypt and the development of Egyptology are momentous events in intellectual and cultural history. The history of Egyptology is the story of the people, famous and obscure, who constructed the picture of ancient Egypt that we have today, recovered the Egyptian past while inventing it anew, and made a lost civilization comprehensible to generations of enchanted readers and viewers thousands of years later. This, the first of a three-volume survey of the history of Egyptology, follows the fascination with ancient Egypt from antiquity until 1881, tracing the recovery of ancient Egypt and its impact on the human imagination in a saga filled with intriguing mysteries, great discoveries, and scholarly creativity